THE ROLE AND PLACE OF INFORMATION PROTECTION IN THE PROGRAM OF TRAINING OF IT-SPECIALISTS - Andrey I. Volkov; Alla Yu. Ermakova (Статистика и экономика)
This article discusses the importance of issues related to the protection of information in the preparation of modern information technology specialists. Notes the importance of studying IT-specialists of this perspective and the need for an integrated approach to the selection and/or development of information security systems. Define the content of training programs on information security, as well as the amount of knowledge in the field of mathematics and information technologies needed for the development of this program. Formulated requirements to the results of development of the program and noted the need to include the protection of information in coursework and final qualifying work.